PENINGKATAN KUALITAS PEMBELAJARAN APRESIASI PUISI MELALUI STRATEGI CONTEXTUAL TEACHING AND LEARNING PADA SISWA KELAS V SD NEGERI JONO 2 KECAMATAN TANON SRAGEN TAHUN 2010 - SUDARMOJO, AGUS (2011)
This research is describing the improvement of poem appreciation of the Student of 5 Grade at SD Negeri Jono 2 Kecamatan Tanon Sragen Tahun 2010 and describing the improvement of students activities in teaching poem appreciation using Contextual Teaching and Learning Strategy of the Student of 5 Grade at SD Negeri Jono 2 Kecamatan Tanon Sragen Tahun 2010. This research is using an Action research by giving the students examination test. The first score is as the data to be done and taken as different teqnique used in cycle 1.2 ad 3.the score taken from the first test . How to improve the understanding of the Improvement of Learning Quality of Poem Appreciation using Contextual Teaching and Learning Strategy. In this research, the act is divided into four part those are planning, action, observation, and reflection. This part is as completing the next cycle until the standard competency gained. The first cycle followed by 14 students with 42, 86% score achieved to standard competency. The improvement done in the second cycle showed that 57,15% gained the standard competency. The last result showed that there were 38 students got 65,00 or more. Individually the students have got the standard competency.The mean was 79,14. The standart competency got 100%. Based on the result it was known that the KKM used as the indicator has been reached.